2014
DOI: 10.1097/jto.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study on the Incidence of Bone Metastasis (BM) and Skeletal-Related Events (SREs) in Patients (pts) with Stage IIIB and IV Lung Cancer—CSP-HOR 13

Abstract: Background:Bone metastasis (BM) is a frequent complication in patients with advanced lung cancer and it causes skeletal-related events (SREs). Our study aim is to prospectively investigate the incidence of BM, incidence and types of SRE, and predictive factors of BM and SREs.Methods:Newly diagnosed, advanced non–small-cell lung cancer (NSCLC) or small-cell lung cancer (SCLC) patients were enrolled into the study. Patients were followed up every 4 weeks to monitor the development of SREs. Treatment for lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 26 publications
5
38
1
Order By: Relevance
“…In our study, bone metastases were found in 26.2% of all patients with SCLC and 34.3% of the patients with SCLC-ED. These results are also consistent with other previous reports that bone metastases are present in around 20% of all SCLC and 40% of SCLC-ED patients [8,9,10]. …”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In our study, bone metastases were found in 26.2% of all patients with SCLC and 34.3% of the patients with SCLC-ED. These results are also consistent with other previous reports that bone metastases are present in around 20% of all SCLC and 40% of SCLC-ED patients [8,9,10]. …”
Section: Discussionsupporting
confidence: 83%
“…We reported a 34.4% rate of SREs in patients with SCLC with bone metastases. In agreement with the results of other studies, the incidence of SREs in our study in SCLC was lower than that reported for NSCLC [3,10]. Shorter survival might be the reason for a lower incidence of SREs in SCLC.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations